Integrating Indonesian Local Wisdom into Tertiary EFL Writing Instruction: Practices, Challenges, and Opportunities - Safnidar Siahaan; Isnaini Eddy Saputro; Nurfisi Arriyani; Sri Lestari; Turab Hussain (Yayasan Keluarga Guru Mandiri, 2025)
This study was initiated to support English as a Foreign Language (EFL) lecturers in enhancing culturally responsive writing instruction by integrating elements of Indonesian local wisdom. Recognizing the need to strengthen students’ cultural identity and moral values through language learning, this initiative aimed to explore current practices, benefits, and challenges faced by lecturers in embedding local content into academic writing tasks. A qualitative-descriptive approach was employed, with data collected through a questionnaire completed by 30 English as a Foreign Language (EFL) lecturers from various Indonesian universities. Findings revealed that a majority of lecturers incorporate proverbs, folktales, traditional events, and cultural values, primarily through descriptive, narrative, and argumentative essays. These practices not only improve students’ linguistic and cognitive skills but also foster reflective thinking and cultural pride. However, lecturers reported several challenges, including limited resources, curriculum constraints, and lack of professional training. The results promote a more localized and meaningful approach to EFL writing instruction, empowering both educators and learners to preserve and reflect on Indonesia’s rich cultural heritage. Moreover, this study contributes to the broader discourse on decolonizing EFL curricula and offers a replicable model for culturally sustaining pedagogy in other multilingual, multicultural contexts.